Wielkosc asymetrii wskazników silowych i szybkosciowo-silowych konczyn dolnych u narciarzy zjazdowców - Bujas, P.; Tchorzewski, D.; Jaworski, J. (Journal of Kinesiology and Exercise Sciences, 2012)
The phenomenon of functional asymmetry in sports has significant influence on performance in sports. In individual cases, especially in those sports disciplines that are highly symmetric, functional asymmetry may hamper the achievement of success. In addition, significant asymmetry may become a foundation for numerous injuries. Aim of the study. The aim of the study was to examine the level of functional asymmetry of the lower limbs in alpine skiers. Material and methods. Three adolescent girls and eight adolescent boys participated in the study. During the tests, the level of the asymmetry of participants` lower extremities was assessed while performing motor tasks that required use of fitness abilities. The following indicators were studied: maximum force and the relative force developed under isometric contraction (knee joint and hip joint extensors) and kinematic indicators describing a countermovement jump (CMJ) on the force platform. The results for dominant and non-dominant limbs were analyzed separately. Results. In most the subjects, the asymmetry coefficient was around 10% or exceeded this value. The direction of asymmetry points to the stronger left knee extensor muscle. Individuals with knee extensors that have higher asymmertry can be characterized by lower asymmetry of the hip extensors. Analysis of the mean values indicates significant differences between the asymmetry coefficients determined for the hip joints and the absence of such differences for the knee joints. Analysis of the jump results reveals symmetry index (SI) values at the level of 20% or above, thus indicating significant asymmetry. The direction of the asymmetry confirms the dominance of the left lower limb. Conclusions. A significant asymmetry of strength abilities is characteristic for young alpine skiers. This could become an obstacle for their further development, but it could also give direction for further actions focused on achieving symmetry.